Rancang Bangun Sistem Informasi Distribusi Air Minum Dalam Kemasan Dengan Model Arus Jaringan Pada CV. Sumber Nadi Jaya - Perdhana, Angga Agia; Supriyanto, Antok; Sulistiowati, Sulistiowati (Jurnal JSIKA, 2012)
CV. Sumber Nadi Jaya as one water bottling company in Bali which have many competitors, is still experiencing difficulties in the distribution. Company’s Operational distribution practices is not beneficial because delivery is carried out in the conventional way and based on driver’s experience on the road. This often led to some customers not receiving bottled water gallon or gallon is received does not match the number of gallons for gallons routine because the number of gallon available on the vehicle is run out after distributed on previous customer. This research used a network flow method, because this method can model the distribution pattern of bottled drinking water, where it is in line with the problems discussed in this case the completed information distribution system that regulates the delivery of bottled drinking water to customers, so it can maximize delivery in a single delivery, and minimize the number of customers who do not receive a gallon of bottled drinking water. Keyword: systems, distribution, bottled drinking water, gallons, CIH